Analysis of Factors Affecting Potential Drug Interactions in Outpatient Hypertension Patients at Dr. Iskak Tulungagung Hospital: Analisis Faktor-Faktor yang Mempengaruhi Potensi Interaksi Obat pada Pasien Hipertensi Rawat Jalan di RSUD Dr. Iskak Tulungagung - Esti Ambar Widyaningrum; Helda Yuli Hermayanti; Binti Muzayyanah; Shofiatul Fajriyah; Fentyana Dwi Rilawati; Sugiyartono Sugiyartono (Universitas Tadulako, 2026)
Background: The global prevalence of hypertension continues to rise, with projections indicating that approximately 29% of adults will be affected by 2025. Hypertension is often accompanied by comorbidities and complications. Hypertension treatment usually involves more than one drug or polypharmacy, increasing the risk of potential interactions. Objective: To examine the association between polypharmacy and potential drug-drug interactions in outpatient hypertensive patients. Material and Method: Retrospective observational study using a purposive sampling technique. A total of 96 patients were included from January-December 2023. The instruments used were medical records, the Drugs Interaction Checker application on the Drugs.com application, and Medscape. Results: Most patients were male (59.38%) and aged 56–65 years (37.50%). Polypharmacy was observed in the majority of patients, with major polypharmacy (>4 drugs) accounting for 48.96%. Potential drug interactions were identified in 65.63% of patients. Pharmacodynamic interactions were more common (58.57%) than pharmacokinetic interactions (41.43%), with moderate severity predominating (78.09%). The number of medications and comorbidities were significantly associated with potential drug interactions (p < 0.05). Conclusion: The number of drugs and the number of comorbidities affect the potential for drug–drug interactions in outpatients with hypertension at Dr. Iskak Tulungagung Hospital.